Detrimental role of pericyte Nox4 in the acute phase of brain ischemia. Issue 6 (June 2016) - Nishimura, Ataru; Ago, Tetsuro; Kuroda, Junya; Arimura, Koichi; Tachibana, Masaki; Nakamura, Kuniyuki; Wakisaka, Yoshinobu; Sadoshima, Junichi; Iihara, Koji; Kitazono, Takanari
Pericytes are mural cells abundantly present in cerebral microvessels and play important roles, including the formation and maintenance of the blood–brain barrier. Nox4 is a major source of reactive oxygen species in cardiovascular cells and modulate cellular functions, particularly under pathological conditions. In the present study, we found that the expression of Nox4 was markedly induced in microvascular cells, including pericytes, in peri-infarct areas after middle cerebral artery occlusion stroke models in mice. The upregulation of Nox4 was greater in a permanent middle cerebral artery occlusion model compared with an ischemia/reperfusion transient middle cerebral artery occlusion model. We performed permanent middle cerebral artery occlusion on mice with Nox4 overexpression in pericytes (Tg-Nox4). Infarct volume was significantly greater with enhanced reactive oxygen species production and blood–brain barrier breakdown in peri-infarct areas in Tg-Nox4, compared with littermate controls. In cultured brain pericytes, Nox4 was significantly upregulated by hypoxia and was promptly downregulated by reoxygenation. Phosphorylation of NFκB and production of matrix metalloproteinase 9 were significantly increased in both cultured pericytes overexpressing Nox4 and in peri-infarct areas in Tg-Nox4. Collectively, Nox4 is upregulated in pericytes in peri-infarct areas after acute brain ischemia and may enhance blood–brain barrier breakdown through activation of NFκB and matrix metalloproteinase 9, thereby causing enlargement of infarct volume.